A Simple and Sensitive UPLC–UV Method for Simultaneous Determination of Isoniazid, Pyrazinamide, and Rifampicin in Human Plasma and Its Application in Therapeutic Drug Monitoring - Jiang, Zhimei; Huang, Liang; Zhang, Lingli; Yu, Qin; Lin, Yunzhu; Fei, Haotian; Shen, Hongxin; Huang, Hong (Frontiers in Molecular Biosciences, 2022)
As the first-line clinical drugs for tuberculosis (TB), isoniazid (INH), pyrazinamide (PZA), and rifampicin (RMP) are playing important roles for preventing the rapid spread of TB. Precise quantification of these drugs in biological samples is crucial to evaluate or improve the efficacy of advanced TB drug delivery systems, which are designed for reducing drug resistance, minimizing side effects, etc. Herein, a simple and sensitive method based on UPLC–UV was established and investigated for simultaneous quantification of PZA, INH, and RMP in human plasma and was applied to anti-TB drug therapeutic drug monitoring. The analytes were implemented on an HSS T3 C18 column at 40°C. The separation was performed with a gradient elution with methanol–acetonitrile–water (3:3:94) at 0.1 ml/min. The analysis only involved plasma with a small volume of 100 µL and a rapid one-step protein precipitation with methanol–acetonitrile (1:1). The results showed that the calibration curves for INH, PZA, and RMP were linear in a range of 0.5–20 μg/ml, 5–60 μg/ml, and 5–60 μg/ml, respectively. The intra- and inter-day precisions were both smaller than 15%, and the lower limit of quantitation (LLOQ) was identifiable and reproducible at 0.5 μg/ml for INH and 5 μg/ml for both PZA and RMP, respectively. The target drugs in plasma were stable after 21 days of storage at −80°C. The results indicated that our developed method is suitable for the simultaneous monitoring of INH, PZA, and RMP in human plasma.